Perilaku Konsumsi Kopi, Kualitas Tidur, dan Status Gizi pada Remaja: Systematic Review - Ashriady Ashriady; Hasniaty Hasniaty; Yasirul Muntaha; Abbas Mahmud; Hasma Hasma (Mando Care Jurnal, 2026)
Coffee consumption among adolescents has increased alongside changes in modern lifestyles and social trends. Excessive caffeine intake may adversely affect sleep quality and nutritional status. This study aimed to systematically review the evidence on the relationship between coffee consumption, caffeine, sleep quality, and nutritional status among adolescents. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed in Garuda Kemdiktisaintek, Google Scholar, PubMed, and ScienceDirect in May 2026. A total of 61 records were identified and screened through duplicate removal, title and abstract screening, and full-text eligibility assessment based on predefined inclusion and exclusion criteria. Finally, nine studies met the eligibility criteria and were included in the review. The findings showed that most adolescents regularly consumed caffeinated beverages and experienced poor sleep quality. The majority of studies reported a significant association between coffee consumption, caffeine intake, and poor sleep quality. Several studies also found associations between caffeine intake and increased body mass index, overweight, obesity, and reduced hemoglobin levels. However, the evidence regarding the association between coffee consumption and nutritional status remains inconsistent. High caffeine intake was also associated with increased stress, anxiety, and reduced academic concentration. In conclusion, excessive coffee consumption and caffeine intake are associated with poor sleep quality among adolescents, whereas their relationship with nutritional status remains inconclusive and requires further investigation.